PANDANGAN GURU TERHADAP INTEGRASI KEARIFAN LOKAL DALAM PEMBELAJARAN SEJARAH: STUDI DESKRIPTIF DI BEBERAPA SMA DI BENGKULU SELATAN DAN KAUR - Een Syaputra (UIN Fatmawati Sukarno Bengkulu, 2019)
Abstract: Teachers’ Perspective of Local Wisdom Integration in History Learning: A Descriptive Study of High School Teachers in Sout Bengkulu and Kaur. The purposes of this research are: 1) to describe teachers’ perspective about term, scope and types of local wisdom; 2) to describe teachers’ perspective of integration local wisdom in high school history learning; and 3) to describe teachers’ perspective of strategy in local wisdom integration in history learning. This research used descriptive qualitative method. Data collection technique used is in-defth interview and interactive model of Milles and Huberman for the data analysis. The result of this research are: 1) local wisdom that is understood by history teacher is about tradition and custom, containing values, and helt for long time from generation to generation. Local wisdom, based on teachers’ perspective, can be categorized into several types, that in firm idea and activity as well as local widom related to relationship between human with God, human and human, and human and environment; 2) the teachers consider that local wisdom is very important to be integrated in history learning for three reasons; to preserve cultural hetitage, local wisdom as a sources of values, and to be used as an enrichment of learning material; 3) in integrating local wisdom in history learning, the teachers have one strategy, that is integration through relevance theme in official predetermined learning material.